Institutional and Policy Analysis of River Basin Management : The Tárcoles River Basin, Costa Rica - Blomquist, William; Ballestero, Maureen; Bhat, Anjali; Kemper, Karin (World Bank, Washington, DC, 2012)
This paper describes and analyzes the effort to institute river basin management in the Tárcoles basin of Costa Rica. Located in west-central Costa Rica, the Tárcoles basin represents 4.2 percent of the nation's total land area, but is home to half the nation's population and the metropolitan area of San José, the nation's capital and largest city. Water management issues include severe water pollution resulting from sewage, industrial waste discharges, agricultural runoff, and deforestation. In the early 1990s a locally-initiated effort established a river basin commission for the Río Grande de Tárcoles (CRGT), which was supported by the central government's environment ministry. Since the late 1990s, however, the DRGT has struggled through changes of leadership, inconsistent support from the central government, and waning participation from basin stakeholders. Despite several programs to arrest deforestation and encourage better industrial and agricultural practices, the basin's water problems continue largely unabated. The Tárcoles case is instructive about both the possibilities and the fragility of efforts to establish integrated water resource management at the river basin level.